Structural Geology Analysis In A Disaster-Prone Of Slope Failure, Merangin Village, Kuok District, Kampar Regency, Riau Province - Yuniarti Yuskar; Dewandra Bagus Eka Putra; Adi Suryadi; Tiggi Choanji; Catur Cahyaningsih (UIR PRESS, 2017)
The geological disaster of landslide has occurred in Merangin Village, Kuok Subdistrict, Kampar Regency, Riau Province which located exactly in the national road of Riau - West Sumatra at Km 91. Based on the occurrence of landslide, this research was conducted to study geological structure and engineering geology to determine the main factors causing landslides. Based on measurement of the structural geology found on research area, there were fractures, faults and fold rocks which having trend of stress N 2380 E, plunge 60, trending NE-SW direction. Several faults that found was normal faults directing N 2000 E with dip 200 trending from northeast-southwest and reverse fault impinging N 550 E with dip 550, pitch 200 trending to the northeast. Fold structures showing azimuth N 2010 E trending southeast-northwest. From geological engineering analysis, the results of scan line at 6 sites that have RQD value ranges 9.4% - 78.7 % with discontinuity spacing 4 - 20 cm. So, It can be concluded that the formed structure was influenced by the extensive northeast-southwest tectonic phase, then continued through north-south tectonic phase, and ended by a tectonic period with directing from northeast-southwest. Rock Mass Rating classification showing value 62 – 76, Which also resulted that rocks in the study area have weathered on the outside but still in good condition (good rock). However, This condition of structure has caused the formation rocks producing weak zone that became one cause of the occurrence of landslides.